Nuevo registro de forcipomyia (Pterobosca) incubans (Macfie) (Diptera: Ceratopogonidae) como parásito de Odonata - Huerta, Herón (Instituto de Ecología, A.C., 2006)
This is the first record of Forcipomyia (Pterobosca) incubans (Macfie) on Dythemis sterilis Hagen (Libellulidae, Odonata) from Veracruz State, Mexico.